Efeito da laserterapia sobre a inflamação pulmonar induzida pela exposição ao formaldeído - Silva, Cristiane Miranda da (2015)
The overall recognition on the growth of lung inflammatory diseases has led to efforts to develop new therapies, particularly for the control of inflammation. Among the therapies used for disorders that affecting the lung, laser therapy has been highlighted, since it is a noninvasive therapy without side effects and anti-inflammatory and antioxidants actions. Studies have shown beneficial effects of low level laser therapy (LLLT) for the treatment of lung diseases, however, the operative mechanisms need to be better understood. Thus, lung inflammation models are important tools to extend the mechanistic knowledge of LLLT. Accordingly, we used Formaldehyde (FA), an environmental and occupational pollutant, which induces airway inflammation. FA is a chemical widely used in many industries, in anatomy laboratories, pathology, histology and is also expelled in cigarette smoke. Lung inflammation induced by exposure to FA is an interesting and important respiratory disease model. For this, we decided to investigate the effects of LLLT in the model of lung inflammation induced by FA, which is already well established. Our studies prioritized the analysis of cells recruited in the lung, blood and bone marrow, the enzyme myeloperoxidase activity, release and gene expression of cytokine, evaluation of lung vascular permeability and mast cell degranulation. Our results suggest a beneficial effect of LLLT on model of lung inflammation induced by pollutant; since the LLLT treatment significantly reduced the number of neutrophils recruited to the lung, lung vascular permeability, mast cell degranulationand also reduced the release of IL-6 and TNF levels in the bronchoalveolar lavage fluidassociated with increased release and gene expression of IL-10. This study may provide important information of a possible therapy to minimize the undesirable effects of pollutants on health.